PENGARUH PENILAIAN KINERJA DAN MOTIVASI KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN KLINIK UTAMA PRIMERA CLINICA WILAYAH JAKARTA TIMUR - Edy Sanusi Silitonga (Program Studi Magister Manajemen Fakultas Ekonomi Universitas Krisnadwipayana, 2022)
This study aims to determine the performance appraisal and work motivation on the work productivity of Klinik Utama Primera Clinica Wilayah Jakarta Timur. The type of research used is associative research with quantitative methods. This study uses a saturated sample with a total sample of 53 employees of Klinik Utama Primera Clinica Wilayah Jakarta Timur. The analytical tool used is partially and simultaneous linear regression. The results showed that simultaneous performance appraisal and work motivation could encourage an increase in employee work productivity, while partially performance appraisal and work motivation could increase the work productivity of Klinik Utama Primera Clinica Wilayah Jakarta Timur.